Lifestyle Factors Rather Than Helicobacter pylori Infection or Estradiol Level are Associated With Osteopenia in Japanese Men. Issue 3 (1st May 2019) - Chinda, Daisuke; Shimoyama, Tadashi; Sawada, Kaori; Iino, Chikara; Sakuraba, Hirotake; Nakaji, Shigeyuki; Fukuda, Shinsaku
Although decreased calcium absorption, decreased bone formation, alcohol drinking, and smoking have been considered as causes of osteopenia in men, the cause is unknown in half of the cases. Many reports highlighted the association between Helicobacter pylori infection and osteoporosis, mainly in East Asia and Japan. To identify relevant factors of osteoporosis in men, we examined estrogen and calcium intakes and other lifestyle factors together with gastric mucosal atrophy caused by Helicobacter pylori infection. This study is a cross-sectional study design of 268 healthy men who underwent general medical examinations. Multivariate analysis was performed, with age, body mass index, smoking habit, drinking habit, exercise habit, estradiol level, calcium intake, and Helicobacter pylori infection and its associated gastric mucosal atrophy as the independent variables and the presence of osteopenia as the dependent variable. The adjusted odds ratio was 0.74 (95% Confidence Interval [0.29, 1.90], p = .531) and 1.31 (95% Confidence Interval [0.54, 3.21], p = .552), when Helicobacter pylori infection was positive without and with gastric mucosal atrophy, respectively. Helicobacter pylori infection and gastric mucosal atrophy were not significant factors. Low body mass index, smoking habit, and low calcium intake were significantly associated with decreased bone density. In conclusion, Helicobacter pylori infection was not a significant risk, whereas low body mass index, current smoking, and lower calcium intake had a significant influence on the development of osteopenia in men.